1974
DOI: 10.1128/aem.28.3.435-438.1974
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the BACTEC System with Blind Subculture for the Detection of Bacteremia

Abstract: One thousand blood specimens were cultured in BACTEC vials containing modified Columbia broth in aerobic, anaerobic, and hypertonic formulations. Radiometric readings and subcultures were performed on aerobic and hypertonic vials at 24 h and 7 days, and on anaerobic vials at 48 h and 7 days. Significant numbers of false-positive BACTEC readings were obtained. Although all positive cultures were eventually detected by the BACTEC, approximately 20% of blood specimens yielding positive subcultures at 24 h did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
1

Year Published

1980
1980
1992
1992

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 3 publications
1
15
1
Order By: Relevance
“…For these reasons, several authors have advocated the use of either subcultures or Gram stains of macroscopically negative blood culture bottles after a 1-or 2-day incubation period and again before the culture is assigned a negative or no growth result after 7 or 14 days of incubation (1, 2, 13). Even when radiometric methods are employed to detect microorganisms in blood culture, "blind" subcultures are needed for optimal recovery and rapid detection of microorganisms (3). A comparative study evaluating the use of subculture, Gram stain, and macroscopic methods indicated that Gram stain and subculture first detected the presence of microorganisms in 23 and 12% of positive cultures, respectively (2).…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, several authors have advocated the use of either subcultures or Gram stains of macroscopically negative blood culture bottles after a 1-or 2-day incubation period and again before the culture is assigned a negative or no growth result after 7 or 14 days of incubation (1, 2, 13). Even when radiometric methods are employed to detect microorganisms in blood culture, "blind" subcultures are needed for optimal recovery and rapid detection of microorganisms (3). A comparative study evaluating the use of subculture, Gram stain, and macroscopic methods indicated that Gram stain and subculture first detected the presence of microorganisms in 23 and 12% of positive cultures, respectively (2).…”
Section: Discussionmentioning
confidence: 99%
“…Routine blind subcultures are not specifically recommended by the manufacturer of the BAC-TEC instrument. However, others (4,20) have previously noted the need for blind subcultures to increase the recovery of certain bacteria. Our study confirms a report by Rosner (20) that subcultures are also necessary to increase the recovery of some yeast strains, since although the instrument did not detect their presence in 17 bottles within the 7 days, they were readily isolated by conventional methods from the same bottles.…”
Section: Detection Of Yeast Septicemiamentioning
confidence: 99%
“…Moreover, these studies were done before acridine orange staining had been recognized as a useful early screening method (12,14,23). Reports that radiometric culture bottles grew baçteria despite negative growth readings (1,3,5,18) and that some radiometric culture bottles had high radiometric readings in the absence of bacteria (2-4, 17,22,25) further suggested that a controlled comparison with conventional media was needed.…”
mentioning
confidence: 99%